Institutional responses to academic literacy challenges: An in-house test as an alternative for assessing academic literacy levels - Drennan, Laura Maria; Joubert, Michelle; Weideman, Albert (Journal for Language Teaching, 2024)
The COVID-19 pandemic brought about disruptions to the administration of conventional academic literacy tests, which necessitated alternative ways of identifying students in need of literacy support. In response to this disruption, an existing in-house test was identified as a potential alternative for measuring incoming students’ ability to handle the demands of academic discourse. Such an alternative was necessary for the effective identification of students needing additional academic literacy support and their placement in appropriate faculty-specific literacy courses. Although the first round of institutional piloting deemed the online version of the test appropriate for being employed for these purposes, a further administration of the test was conducted to confirm whether the traditional (pencil-and-paper) version of the test yielded similar results and whether the quality of the test is such that it is appropriate for implementation at an institutional level. This paper compares the results of these two administrations of the test and reflects on the potential value of such an in-house test to achieve and enhance the synchrony between assessment, curriculum and teaching, building on earlier work on this.